Investigação do fenômeno oscilatório na síntese de filmes de Nb2O5 em PEO. - Batista, Jonata Rodrigues Dias (2024)
This research focuses on the process of plasma electrolytic oxidation (PEO), a type of anodization that has been extensively studied due to the wide range of applications its coatings provide to materials, such as corrosion resistance, adhesion, and mechanical stress resistance, and catalytic processes. PEO differentiates from conventional anodization by employing significantly higher voltages in an electrochemical cell, resulting in the generation of ionized gas at the surface of the working electrode, in the specific case of this study, niobium. This phenomenon imparts unique properties to the resulting oxide film. The primary focus of this research was to investigate a previously undocumented behavior on a specific condition: the occurrence of low-frequency and high-amplitude oscillations during the anodization process of niobium in different types of electrolytes. Data was collected using a system comprising a direct current source in galvanostatic mode, electrolyte temperature control, and an in-situ data acquisition and recording system, generating potentiostatic curves of voltage versus time. Three approaches were taken to explore this phenomenon. The first involved anodization in three distinct electrolytes (H3PO4, KOH, and C2H2O4) at two temperatures to identify conditions conducive to oscillation manifestation. The second approach varied current densities (5, 10, and 20 mA/cm2) in a C2H2O4 electrolyte, revealing that increased current density correspondingly elevated oscillation frequency, accelerating the process kinetics. Lastly, anodization was interrupted at different time points on the voltage-time curve to understand better the evolution of oxidized film growth in the presence of oscillations. The obtained samples were analyzed through scanning electron microscopy (SEM) to visualize cross-sectional and surface images of the porous film, as well as X-ray diffraction (XRD) to determine the crystal structure. Among notable results, it was observed that oscillations occur under specific combinations of temperature and electrolyte, indicating a complex interplay between these parameters. Additionally, an increase in current density was observed to intensify oscillation frequency, suggesting a direct influence of current density on process kinetics. Furthermore, in the approach investigating the oxide film at different anodization times, cross-sectional analysis unveiled the formation of thin films with grooves and rough surfaces. Surface analysis indicated a trend of pore size reduction on the surface as each oscillatory cycle advanced, suggesting a dynamic process of dissolution and subsequent pore filling over time, which plays a crucial role in modulating the oscillatory behavior. Structural analysis revealed that all samples exhibited the same orthorhombic Nb2O5 crystal structure, suggesting that the oscillatory phenomenon does not affect the crystal structure of the film. This research comprehensively investigates the amplitude and frequency oscillations during the plasma electrolytic oxidation process on niobium. The findings hold the potential to contribute to the understanding of this poorly understood phenomenon with implications for the control and optimization of anodization processes across various applications.